Experimental and analytical study of steel–PVA hybrid fiber-reinforced mortar containing CaCO3 whiskers subjected to freeze–thaw cycles - Liu, Zixing; Cao, Mingli; Xie, Chaopeng (Archives of Civil and Mechanical Engineering, 2022)
In high latitude and altitude areas, cement-based composite is subject to freeze–thaw cycles. The uniaxial compressive properties and microstructure of steel–PVA fiber reinforced cement mortar incorporating CaCO 3 whiskers (SPFRC-CW) before and after freeze–thaw cycles were studied in this paper. The relative mass loss (RML), relative ultrasonic pulse velocity (RUPV), and the stress–strain relationship of frost–damaged SPFRC-CW was measured for a study of the durability and mechanical property degradation rules. A damage model was established considering the freeze–thaw cycles and CW volume fraction for SPFRC-CW, which demonstrated decent consistency between theoretical and experimental curves. The microstructure was analyzed using an optical microscope (OM), scanning electron microscope (SEM), vacuum epoxy impregnation (VEI), and mercury intrusion porosimetry (MIP). The results suggest that the physical and mechanical properties of SPFRC-CW decreased with prolonged freeze–thaw cycles. The better frost resistance of SPFRC was related to the improved pore structure because of the presence of CW, as per the results of VEI and MIP.